The National Network of Perinatal Quality Collaboratives: Opportunity to Enhance the Care and Outcomes for Mothers and Babies. Issue 3 (May 2018) - Simpson, Kathleen Rice
Abstract : Clinicians, scientists, public health experts, and patients working together in state-wide perinatal quality collaboratives can significantly improve care and outcomes for mothers and babies. Supporters of these efforts include the Centers for Disease Control and Prevention, the March of Dimes Foundation, and the National Institute for Children's Health Quality.